Dispersal of Agrilus planipennis (Coleoptera: Buprestidae) From Discrete Epicenters in Two Outlier Sites. Issue 2 (17th November 2014) - Siegert, N. W.; McCullough, D. G.; Williams, D. W.; Fraser, I.; Poland, T. M.; Pierce, S. J.
Abstract : Emerald ash borer, Agrilus planipennis (Fairmaire) (Coleoptera: Buprestidae), a phloem-feeding beetle native to Asia, has become one of the most destructive forest pests in North America. Since it was first identified in 2002 in southeast Michigan and Windsor, Ontario, dozens of isolated A. planipennis populations have been discovered throughout Michigan and Ontario, and in 12 other states and the province of Quebec. We assessed realized A. planipennis dispersal at two discrete outlier sites that originated 1 yr and 3 yr earlier from infested nursery trees. We systematically sampled ash trees within an 800 m radius of the origin of each infestation to locate galleries constructed by the progeny of dispersing A. planipennis adults. Our sampling identified eight trees at the 1 yr site infested with a mean ± SE of 11.6 ± 8.4 A. planipennis larvae and 12 trees at the 3 yr site with 25.8 ± 11.1 larvae per meter squared. Dendroentomological analysis indicated that A. planipennis populations were predominantly undergoing a 2 yr (semivoltine) life cycle at both sites. Colonized trees were found out to 638 and 540 m from the epicenters at the 1 yr and 3 yr sites, respectively. Logistic regression was used to determine whether the likelihood of A. planipennis colonization was affected by wind direction, ash phloem abundance, distance from the epicenter, or land-use type (i.e., wooded, residential, agricultural, or urban). Results show that the probability of A. planipennis colonization was significantly affected by ash phloem abundance and decreased with distance from the epicenter.